New approach to organ transplantation based on the fetal allograft. - Finn, R (1978)
A new approach to organ transplantation that may be particularly applicable to kidney transplantation is suggested by analogy with the immunological mechanism responsible for the survival of the fetal allograft. The method concerns identifying donor-recipient tissue compatibility by use of the two-way mixed lymphocyte reaction (MLR), in which reacting cells from patients awaiting transplants are primed with phytohaemagglutinin (PHA) and stored. When a donor becomes available, these PHA-primed cells may then be tested against donor lymphocytes, possibly giving a result within 36 hours. Immunosuppressive agents occurring naturally in pregnancy, such as alpha-fetoprotein and chorionic gonadotrophin, may eventually replace standard immunosuppressive treatment with potentially toxic regimens in transplant recipients. If the results of the two-way MLR using PHA-primed cells are shown to be comparable to those of the standard two-way MLR graft survival may be successful in 80% of cases.